PENGARUH MODEL AUDITORY INTELECTUALLY REPETITION BERBASIS SOCIO-SCIENTIFIC ISSUE TERHADAP KETERAMPILAN BERPIKIR KRITIS(THE IMPACT OF THE AUDITORY INTELLECTUALLY REPETITION (AIR) MODEL BASED ON SOCIO-SCIENTIFIC ISSUES ON CRITICAL THINKING SKILLS) - Mukhlish, Muhammad; Paidi, Paidi (Universitas Negeri Yogyakarta, 2025)
Critical thinking skills are one of the four skills that must be prepared in the 21st century. The results of observations in one of the leading high schools in Tolitoli, Central Sulawesi, showed that low critical thinking skills were likely caused by using learning models that were not yet relevant. One effort to develop students’ critical thinking skills is through the Auditory Intellectually Repetition (AIR) model based on Socio-Scientific Issues (SSI). This study aims to determine the effect of the SSI-based AIR model on students’ critical thinking skills about environmental pollution materials. This type of research is a quantitative quasi-experimental study with a Pre-test-Post-test control group design. The research sample was selected through cluster random sampling from the population of four Grade X science program classes. After randomization, a research sample of 72 out of 144 students was selected, and they were divided into two groups: the experimental group (SSI-based AIR) and the control group (discovery learning). Experts have validated the research instrument used. The research data analysis used the independent sample t-test or Mann-Whitney test. The results of the Mann-Whitney test analysis showed a significance value (two-tailed) of 0.012 (p 0.05). Based on these results, it can be concluded that applying the SSI-based AIR model has a positive impact on students’ critical thinking skills regarding environmental pollution materials. Teachers can utilize the findings of this study as an alternative to employing innovative methods in their classrooms.